Sulfide‐Inhibiting Growth of Lead Sulfide Rods Array Film from Micron to Nano for NIR Photodetector. Issue 10 (18th March 2022) - Yan, Ruiyang; Yang, Chan; Feng, Shuanglong; Li, Shangkun
Abstract : In general, the growth rate of lead sulfide (PbS) crystals in the solution is fast, and it is difficult to obtain nanosized structure films without the presence of inhibitors. Herein, highly crystalline 1D single‐crystal PbS nanorods array on the graphene substrate is prepared in the solution containing a high‐concentration sulfur ion as the inhibitors by electrochemical atomic layer epitaxy (ECALE) method. Meanwhile, the diameter of the PbS array from micrometers to nanometers can be controlled by adjusting the ratio of lead and sulfur. Through polarization studies on graphene substrates, the critical role of Au–thiolate in the vertical growth of PbS nanorod is controlled. Finally, the PbS array–graphene heterostructure photodetector presents an extraordinary photoresponsivity in 1.55 μm at room temperature. Abstract : Herein, highly crystalline one dimension single‐crystal lead sulfide (PbS) rods array from micrometers to nanometers is prepared by electrochemical atomic layer epitaxy (ECALE) method by adjusting the lead–sulfur ratio. The formation mechanism and interface state of PbS array are further explored. The PbS array–graphene heterostructure photodetector shows an extraordinary photoresponsivity in 1.55 μm at room temperature.